Genetic and Phenotypic Variability between Families with Hereditary Protein S Deficiency - Rezende, Suely M.; Lane, David A.; Zöller, Bengt; Mille-Baker, Blandine; Laffan, Mike; Dahlbäck, Björn; Simmonds, Rachel E. (Thrombosis and Haemostasis, 2002)
While many mutations thought to result in protein S (PS) deficiency are known, there have been few attempts to relate genotype expression with plasma phenotype. We have investigated the nature and consequence of PS gene (PROS1) mutations in 17 PS-deficient families who presented with mixed type I and type III phenotypes. Seven different mutations were found in nine families: delG-34 (STOP codon at –24), Val-24Glu, Arg49Cys, Asn217Ser, Gly295Val, +5 G to A intron j and His623Pro. PS wild type (PSWT) and the five missense mutants were transiently expressed in COS-1 cells. All mutants expressed lower (p<0.05) PS antigen compared to PSWT (100%). The mutants Val-24Glu, Gly295Val and His623Pro expressed very low/undetectable PS levels. The mutant Asn217Ser produced around 30% of PSWT, while the mutant Arg49Cys had the highest PS levels (around 50%). Metabolic labelling and pulse-chase experiments showed that all of the mutants had impaired secretion, but this was of variable severity. Also, enhanced intracellular degradation of unsecreted material was found for all mutants. There was a strong correspondence between plasma free PS levels in carriers of the mutations, secreted PS from transfected COS-1 cells and labelled PS from 24 h conditioned medium in pulse-chase experiment. We conclude that the magnitude of secretion defect depends on the nature of the PROS1 mutation and influences the level of free PS in plasma. It is likely that the severity of the secretion defect will determine the risk for venous thrombosis.
Keywords: Protein S; venous thrombosis; thrombophilia